Understanding Fatwahs & the Concerns of Iraqi Youth Today - Butt, Sophia (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Muslims believe that Qur’anic revelations and the sayings (or hadith) of the Prophet Muhammad provide a code of life for this world, and the hereafter. Through the Holy Qur’an, His Prophet, and the Prophet’s Progeny, Allah informed Muslims that it is incumbent upon them to both pursue knowledge, and to act upon it with wisdom. In an attempt to obey this command of the Almighty, followers of Islam who seek to understand Divine Scriptures with due diligence also eventually realise the limits to their understanding, even when endeavouring to decode the apparently simplest of Qur’anic verses, as they often have an underlying complexity to their exegesis. Thus, unlike Sunni Muslims, the Shi’a followers of the Ahlulbayt appreciate both the importance and necessity of taqlīd – that is, deferring to appointed jurisprudents for learned and scholarly interpretations of the Holy Texts, the teachings of the Prophet Muhammad and what are considered to be his infallible descendants from his daughter, Fatima Zahra. However, to what extent are the edicts, or fatwahs, issued by contemporary Islamic jurisprudents in alignment with the beliefs and concerns of the youth of today, specifically Iraqis?